Computational and Pharmacological Evaluation of Ferrocene-Based Acyl Ureas and Homoleptic Cadmium Carboxylate Derivatives for Anti-diabetic Potential - Bano, Shahar; Khan, Arif-ullah; Asghar, Faiza; Usman, Muhammad; Badshah, Amin; Ali, Saqib (Frontiers in Pharmacology, 2018)
We investigated possible anti-diabetic effect of ferrocene-based acyl ureas: 4-ferrocenyl aniline (PFA), 1-(4-chlorobenzoyl)-3-(4-ferrocenylphenyl) urea (DPC1), 1-(3-chlorobenzoyl)-3-(4-ferrocenylphenyl) urea (DMC1), 1-(2-chlorobenzoyl)-3-(4-ferrocenylphenyl) urea (DOC1) and homoleptic cadmium carboxylates: bis (diphenylacetato) cadmium (II) (DPAA), bis (4-chlorophenylacetato) cadmium (II) (CPAA), using in-silico and in-vivo techniques. PFA, DPC1, DMC1, DOC1, DPAA and CPAA exhibited high binding affinities (ACE ≥ -350 Kcal/mol) against targets: aldose reductase, peroxisome proliferator-activated receptor γ, 11β-hydroxysteroid dehydrogenase-1, C-alpha glucosidase and glucokinase, while showed moderate affinities (ACE ≥ -250 Kcal/mol) against N-alpha glucosidase, dipeptidyl peptidase-IV, phosphorylated-Akt, glycogen synthase kinases-3β, fructose-1,6-bisphosphatase and phosphoenolpyruvate carboxykinase, whereas revealed lower affinities (ACE < -250 Kcal/mol) vs. alpha amylase, protein tyrosine phosphatases 1B, glycogen phosphorylase and phosphatidylinositol 3 kinase. In alloxan (300 mg/Kg)-induced diabetic mice, DPAA and DPC1 (1-10 mg/Kg) at day 1, 5, 10, 15 and 20th decreased blood glucose levels, compared to diabetic control group and improved the treated animals body weight. DPAA (10 mg/Kg) and DPC1 (5 mg/Kg) in time-dependent manner (30-120 min.) enhanced tolerance of oral glucose overload in mice. DPAA and DPCI dose-dependently at 1, 5 and 10 mg/Kg decreased glycosylated hemoglobin levels in diabetic animals, as caused by metformin. These results indicate that aforementioned derivatives of ferrocene and cadmium possess anti-diabetic potential.